1999
DOI: 10.1002/(sici)1096-8652(199901)60:1<70::aid-ajh12>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Acquired factor VIII inhibitors?successful treatment with an oral outpatient regimen

Abstract: A rare cause of a spontaneous, life threatening coagulopathy in adults is the development of autoantibodies to factor VIII. We recently had the opportunity to treat seven patients with this disorder. After stabilization, they were given a regimen consisting of prednisone and oral cyclophosphamide. All patients had a complete response to treatment. The median time to response was three weeks. Durable remissions were achieved, making this oral regimen an acceptable treatment for this disorder. Am. J. Hematol. 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 3 publications
2
21
0
1
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12][13][14][15][16] This is likely to have led to the reporting of more severely affected and younger patients. This view is supported by the finding that the patients reported in this series 1,20,21 are significantly older than previously reported, have a lower incidence of pregnancy-related acquired hemophilia, and a higher incidence of malignancy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[4][5][6][7][8][9][10][11][12][13][14][15][16] This is likely to have led to the reporting of more severely affected and younger patients. This view is supported by the finding that the patients reported in this series 1,20,21 are significantly older than previously reported, have a lower incidence of pregnancy-related acquired hemophilia, and a higher incidence of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 The studies reporting immunosuppressive regimens have almost invariably been singlecenter cohorts that have not included controls. [4][5][6][7][8][9][10][11][12][13][14][15][16] These studies will tend to preferentially report good outcomes as opposed to average or poor outcomes and journals will similarly be more likely to publish good outcome studies. One randomized study published to date found no difference between nonremitters randomized to cyclophosphamide and those that continued with steroids after an initial 3-week course of steroids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The original data of individual patients were described in the articles by Herbst, 33 Lian, 34 Bayer, 35 Shaffer 36 and Huang.…”
Section: Patientsmentioning
confidence: 99%